Developing an Algorithm to Improve Positioning Accuracy of Low-Cost Global Navigation Satellite System Modules - Gunathilaka, Malavige Don Eranda Kanchana; Karunathilaka, Indula; Perera, Nihal (Journal of Applied Geospatial Information, 2023)
Global Navigation Satellite System (GNSS) technology is the most widely used technique for obtaining positioning and navigation information for various applications. However, GNSS is not an error free technology. Differential GNSS techniques are used to mitigate these errors and different commercial brands of GNSS receivers have been developed to avoid some errors where quality and performance depends heavily on the price tag of such advance GNSS receivers due to the fact that technological capabilities adopted and embedded in each single GNSS receiver. There are user cases where the few or more those capabilities has to keep leave behind thereby compromise the cost to benefit ratio. As an alternative to above problem, some low-cost GNSS modules are now available in the market which has quite low position accuracy but can be developed to address unique requirements of some user cases. In practical situations, Real-Time-Kinematic (RTK) positioning systems cannot be used everywhere due to its technical limitations and GNSS receivers use different levels of techniques such as moving baseline system or Satellite Based Augmentation System (SBAS). Further, heading information is also a very important parameter in marine industry for obtaining the vessel’s orientation. This research attempts to assess the capability of u-blox NEO M8N GNSS module for hydrographic surveys by developing a moving baseline GNSS configuration and simple Kalman filter based algorithm. The developed prototype was tested in both static and kinematic observations. The prototype achieved 0.5-2.5 meters of position accuracy at the 95% confidence level in static observations, while it archived around 3 meters of positioning accuracy in kinematic observations. This is a sufficient accuracy for Order 1a, Order 1b and Order 2 standards of hydrographic surveys according to the IHO S-44 guidelines.